Polystyrene nanoplastics disrupt mouse placenta development in a sex-dependent manner - Hanin Alahmadi; Allison Harbolic; Christopher De Oliveira-Cordova; Raulle Reynolds; Michelle Jojy; Courtney Potts; Sofia Doan; Tanvi Mathur; Mohammad Saiful Islam; Melisa J. Andrade; Quinton Smith; Phoebe A. Stapleton; et al. (Reproductive Toxicology, 2026)

Effects of adding plant-based menu options on meat selection frequency: A randomized controlled experiment - Jessica E. Hope; Seth A. Green; Jacob R. Peacock; Maya B. Mathur (Food Quality and Preference, 2026)

Low-dose inorganic arsenic exposure reprograms macrophages differentiation and function toward tumor-promoting phenotypes - Emily J. Illingworth; Sylvia S. Sanchez; Kristal A. Rychlik; Andre Kleensang; Jason Laird; Gabriel A. Lopez-Cecetaite; M. Carolina Rodriguez Steube; Aakriti Mathur; Pritam Sadhukhan; Daniel A. Medina-Cleghorn; Daniel Nomura; Martyn T. Smith; et al. (Environmental Research, 2026)

Prenatal arsenic exposure and gene expression in fetal liver, heart, lung, and placenta - Kristal A. Rychlik; Sylvia S. Sanchez; Chloe Kashiwagi; Jin-Shiung Liao; Aakriti Mathur; Emily J. Illingworth; Andre Kleensang; Alexandra Maertens; Fenna C.M. Sillé (Toxicology, 2026)

Cu isotopes resolve acid mine drainage sources and treatment pathways at the argo tunnel water treatment plant - Molly C. Morgan; Ryan Mathur; Elizabeth A. Holley; Cameron Lasinsky (Chemical Geology, 2026)

Copper isotopic evidence of microbial gold fixation in the Mesoarchean Witwatersrand Basin - Ryan Mathur; Linda Godfrey; Hartwig E. Frimmel; Nathan Yee; David Mossman; Peter Baran; Victor A. Valencia (Geochimica et Cosmochimica Acta, 2025)

Human recreation influences activity of a large carnivore in an urban landscape - Ellen C. Bolas; Adam D. Pingatore; Maya Mathur; Daniel T. Blumstein; Jeff A. Sikich; Justine A. Smith; John F. Benson; Seth P.D. Riley; Rachel V. Blakey (Biological Conservation, 2025)

Laccase mediated transformation of fluoroquinolone antibiotics: Analyzing degradation pathways and assessing algal toxicity - Purvi Mathur; Mandira Kochar; Xavier A. Conlan; Frederick M. Pfeffer; Mukul Dubey; Damien L. Callahan (Environmental Pollution, 2024)

S17-02: The Long-term Impact of Perinatal Exposures on Susceptibility to Immune-mediated Diseases - K.A. Rychlik; E.J. Illingworth; S.E. Attreed; S.S. Sanchez; A. Grant-Alfieri; M.C. Rodriguez Steube; A. Mathur; I.F. Sanchez; C. Tang; M. Suresh; G. Lopez-Cecetaite; P. Sadhukhan; et al. (Toxicology Letters, 2023)

Mutation spectrum and enzyme profiling of G6PD deficiency in neonates of north India: a prospective study - Upasana Bhattacharyya; Preeti Deswal; Sunil Kumar Polipalli; Diksha Sharma; Manpreet Kaur; Madhulika Kabra; Neerja Gupta; Ramesh Agarwal; A. K. Deorari; V. K. Paul; Shevendru Roy; R. K. Sanjeev; et al. (Journal of Genetics, 2023)

Plastome characterization of Musa indandamanensis, an endemic banana in Andaman and Nicobar Islands, India - Satish Maurya; Vitthal T. Barvkar; Ritesh K. Choudhary; Lalji Singh; Mayank D. Dwivedi; Mudavath C. Naik; Gautam A. Ekka; Manish Kandwal; Roshni R. Mathur; Arun K. Pandey (The Nucleus, 2023)

Investigation of metasomatism using Cu, Zn and Fe stable isotopes: Rodingitization of mafic and ultramafic rocks in ophiolites from northern Greece - N. Zaronikola; V. Debaille; A. Rogkala; P. Petrounias; R. Mathur; S. Decrée; P. Pomonis; K. Hatzipanagiotou; B. Tsikouras (Lithos, 2023)

Tricuspid Valve Annuloplasty Alters Leaflet Mechanics - Mrudang Mathur; William D. Meador; Tomasz Jazwiec; Marcin Malinowski; Tomasz A. Timek; Manuel K. Rausch (Annals of Biomedical Engineering, 2020)

Comparing transformation pathways across major economies - R. Schaeffer; A. Köberle; H. L. van Soest; C. Bertram; G. Luderer; K. Riahi; V. Krey; D. P. van Vuuren; E. Kriegler; S. Fujimori; W. Chen; C. He; et al. (Climatic Change, 2020)

The Effect of Downsizing on the Normal Tricuspid Annulus - Mrudang Mathur; William D. Meador; Tomasz Jazwiec; Marcin Malinowski; Tomasz A. Timek; Manuel K. Rausch (Annals of Biomedical Engineering, 2020)

Present status of Catharanthus roseus monoterpenoid indole alkaloids engineering in homo- and hetero-logous systems - Abhishek Sharma; Dhruti Amin; A. Sankaranarayanan; Rajesh Arora; Ajay Kumar Mathur (Biotechnology Letters, 2020)

Salicylic acid and ultrasonic stress modulated gene expression and ginsenoside production in differentially affected Panax quinquefolius (L.) and Panax sikkimensis (Ban.) cell suspensions - Tanya Biswas; Archana Mathur; Vikrant Gupta; Manju Singh; A. K. Mathur (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Toxicity assessment of popular baby skin care products from Indian market using microbial bioassays and chemical methods - A. Nepalia; A. Singh; N. Mathur; S. Pareek (International Journal of Environmental Science and Technology, 2018)

Enhanced expression of ginsenoside biosynthetic genes and in vitro ginsenoside production in elicited Panax sikkimensis (Ban) cell suspensions - Tanya Biswas; Shiv Shanker Pandey; Deepamala Maji; Vikrant Gupta; Alok Kalra; Manju Singh; Archana Mathur; A. K. Mathur (Protoplasma, 2018)

Day-1 INSAT-3DR Vicarious Calibration Using Reflectance-Based Approach Over Great Rann of Kutch - Piyushkumar N. Patel; K. N. Babu; R. P. Prajapati; Vikram Sitapara; A. K. Mathur (Journal of the Indian Society of Remote Sensing, 2018)

Copper-Induced Modulation of Biomass Growth, Physiological Parameters, Bioactive Centellosides, and Expression of Biosynthetic Pathway Genes in an Important Medicinal Herb, Centella asiatica - Archana Prasad; Mamta Kumari; N. K. Srivastava; A. K. Mathur; Archana Mathur (Journal of Plant Growth Regulation, 2018)

INSAT-3D and MODIS retrieved sea surface temperature validation and assessment over waters surrounding the Indian subcontinent - Geetika Tyagi; K. N. Babu; A. K. Mathur; H. A. Solanki (International Journal of Remote Sensing, 2018)

Preclinical evaluation of the Aurora kinase inhibitors AMG 900, AZD1152-HQPA, and MK-5108 on SW-872 and 93T449 human liposarcoma cells - Sandhya Noronha; Lauren A. C. Alt; Taylor E. Scimeca; Omran Zarou; Justyna Obrzut; Brian Zanotti; Elizabeth A. Hayward; Akhil Pillai; Shubha Mathur; Joseph Rojas; Ribhi Salamah; Nalini Chandar; et al. (In Vitro Cellular & Developmental Biology - Animal, 2018)

Gene networks for total number born in pigs across divergent environments - Lucas L. Verardo; Marcos S. Lopes; Pramod Mathur; Ole Madsen; Fabyano F. Silva; Martien A. M. Groenen; Egbert F. Knol; Paulo S. Lopes; Simone E. F. Guimarães (Mammalian Genome, 2017)

A Temporal Study on the Effects of TiO2 Nanoparticles in a Fresh Water Microcosm - Deepak Kumar; A. Rajeshwari; Rajdeep Roy; Sunandan Pakrashi; V. Iswarya; Ida Evangeline Paul; Ankita Mathur; N. Chandrasekaran; Amitava Mukherjee (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

New isotopic evidence bearing on bonanza (Au-Ag) epithermal ore-forming processes - James A. Saunders; Ryan Mathur; George D. Kamenov; Toru Shimizu; Matthew E. Brueseke (Mineralium Deposita, 2016)

The myth of interconnected plastids and related phenomena - Martin H. Schattat; Kiah A. Barton; Jaideep Mathur (Protoplasma, 2015)

Monitoring hospital wastewaters for their probable genotoxicity and mutagenicity - Pratibha Sharma; N. Mathur; A. Singh; M. Sogani; P. Bhatnagar; R. Atri; S. Pareek (Environmental Monitoring and Assessment, 2015)

Erratum to: Re–Os isotope evidence for mixed source components in carbonate-replacement Pb–Zn–Ag deposits in the Lavrion district, Attica, Greece - Paul G. Spry; Ryan D. Mathur; Todd A. Bonsall; Panagiotis Ch. Voudouris; Vasilios Melfos (Mineralogy and Petrology, 2014)

Re–Os isotope evidence for mixed source components in carbonate-replacement Pb–Zn–Ag deposits in the Lavrion district, Attica, Greece - Paul G. Spry; Ryan D. Mathur; Todd A. Bonsall; Panagiotis Ch. Voudouris; Vasilios Melfos (Mineralogy and Petrology, 2014)

Remediation of LNAPL Contaminated Groundwater Using Plant-Assisted Biostimulation and Bioaugmentation Methods - Brijesh K Yadav; Faiz A Ansari; Shreejita Basu; Anuj Mathur (Water, Air, & Soil Pollution, 2014)

An ecogenomic analysis of herbivore‐induced plant volatiles in B rassica juncea - Vartika Mathur; Tom O. G. Tytgat; Cornelis A. Hordijk; Harry R. Harhangi; Jeroen J. Jansen; A. Sankara Reddy; Jeffrey A. Harvey; Louise E. M. Vet; Nicole M. van Dam (Molecular Ecology, 2013)
Upon herbivore feeding, plants emit complex bouquets of induced volatiles that may repel insect herbivores as well as attract parasitoids or predators. Due to differences in the temporal dynamics of individual components, the composition of the herbivore‐induced plant volatile ( HIPV ) blend changes with time. Consequently, the response of insects associated with plants is not constant either. Using Brassica juncea as the model plant and generalist Spodoptera spp. larvae as the inducing herbivore, we investigated herbivore and parasitoid preference as well as the molecular mechanisms behind the temporal dynamics in HIPV emissions at 24, 48 and 72 h after damage. In choice tests, Spodoptera litura moth preferred undamaged plants, whereas its parasitoid Cotesia marginiventris favoured plants induced for 48 h. In contrast, the specialist Plutella xylostella and its parasitoid C. vestalis preferred plants induced for 72 h. These preferences matched the dynamic changes in HIPV blends over time. Gene expression analysis suggested that the induced response after Spodoptera feeding is mainly controlled by the jasmonic acid pathway in both damaged and systemic leaves. Several genes involved in sulphide and green leaf volatile synthesis were clearly up‐regulated. This study thus shows that HIPV blends vary considerably over a short period of time, and these changes are actively regulated at the gene expression level. Moreover, temporal changes in HIPV s elicit differential preferences of herbivores and their natural enemies. We argue that the temporal dynamics of HIPV s may play a key role in shaping the response of insects associated with plants.

Semen quality of environmentally exposed human population: the toxicological consequence - Niraj Pant; A. B. Pant; P. K. Chaturvedi; M. Shukla; N. Mathur; Y. K Gupta; D. K. Saxena (Environmental Science and Pollution Research, 2013)

Health care industries: potential generators of genotoxic waste - Pratibha Sharma; Manish Kumar; N. Mathur; A. Singh; P. Bhatnagar; M. Sogani (Environmental Science and Pollution Research, 2013)

Particulate matter concentration in ambient air and its effects on lung functions among residents in the National Capital Region, India - C. Kesavachandran; B. S. Pangtey; V. Bihari; M. Fareed; M. K. Pathak; A. K. Srivastava; N. Mathur (Environmental Monitoring and Assessment, 2013)

Pathogen-derived resistance using a viral nucleocapsid gene confers only partial non-durable protection in peanut against peanut bud necrosis virus - S. Chander Rao; P. Bhatnagar-Mathur; P. Lava Kumar; A. Sudarshan Reddy; Kiran K. Sharma (Archives of Virology, 2013)

Growth, alkaloid production, rol genes integration, bioreactor up-scaling and plant regeneration studies in hairy root lines of Catharanthus roseus - P Verma; A K. Mathur; K Shanker (Plant Biosystems, 2012)

Initiation of Locomotion in Decerebrate Cats by Pulsed Magnetic Fields Projected onto Spinal Cord Segments - V. D. Avelev; R. Mathur; D. Behari; N. A. Shcherbakova; I. Yu. Dorofeev; A. A. Savokhin; Yu. P. Gerasimenko (Neuroscience and Behavioral Physiology, 2011)

Carbon isotope excursion at Paleocene–Eocene transition in Jaisalmer Basin, western Rajasthan, India - Anil Maheshwari; A. N. Sial; S. C. Mathur; Amita Tripathi (Carbonates and Evaporites, 2010)

Variation of Mo isotopes from molybdenite in high-temperature hydrothermal ore deposits - Ryan Mathur; S. Brantley; A. Anbar; F. Munizaga; V. Maksaev; R. Newberry; J. Vervoort; G. Hart (Mineralium Deposita, 2010)

VEGFR1/CXCR4-positive progenitor cells modulate local inflammation and augment tissue perfusion by a SDF-1-dependent mechanism - Andrew Wragg; Jason A. Mellad; Leilani E. Beltran; Mikhail Konoplyannikov; Hong San; Sherry Boozer; Robert J. Deans; Anthony Mathur; Robert J. Lederman; Jason C. Kovacic; Manfred Boehm (Journal of Molecular Medicine, 2008)

Effects of adolescent fluoxetine treatment on fear-, anxiety-or stress-related behaviors in C57BL/6J or BALB/cJ mice - Maxine Norcross; Poonam Mathur; Abigail J. Enoch; Rose-Marie Karlsson; Jonathan L. Brigman; Heather A. Cameron; Judith Harvey-White; Andrew Holmes (Psychopharmacology, 2008)

Effects of adolescent fluoxetine treatment on fear-, anxiety- or stress-related behaviors in C57BL/6J or BALB/cJ mice - Maxine Norcross; Mathur Poonam; Abigail J. Enoch; Rose-Marie Karlsson; Jonathan L. Brigman; Heather A. Cameron; Judith Harvey-White; Andrew Holmes (Psychopharmacology, 2008)

Fluid inclusion and Re–Os isotopic evidence for hot, Cenozoic mineralization in the central Pennsylvanian Valley and Ridge Province - R. Mathur; L. Mutti; F. Barra; D. Gold; R. C. Smith; A. Doden; T. Detrie; J. Ruiz; A. McWilliams (Mineralogy and Petrology, 2008)

Distribution analysis of salt affected soils under canal and non-canal command area in a part of Etah district, U. P., using remote sensing technique - A. K. Singh; P. K. Singh; B. Lal; A. N. Singh; A. Mathur (Journal of the Indian Society of Remote Sensing, 2008)

An insufficient anti-inflammatory cytokine response in mouse brain is associated with increased tissue pathology and viral load during Japanese encephalitis virus infection - V. Saxena; A. Mathur; N. Krishnani; T. N. Dhole (Archives of Virology, 2008)

A study of air–sea interaction following the tsunami of 26 December 2004 in the eastern Indian Ocean - V. K. Agarwal; A. Mathur; R. Sharma; N. Agarwal; A. Parekh (International Journal of Remote Sensing, 2007)

Flow and High Affinity Binding Affect the Elastic Modulus of the Nucleus, Cell Body and the Stress Fibers of Endothelial Cells - Anshu B. Mathur; William M. Reichert; George A. Truskey (Annals of Biomedical Engineering, 2007)

Land cover classification using multi‐temporal MERIS vegetation indices - J. Dash; A. Mathur; G. M. Foody; P. J. Curran; J. W. Chipman; T. M. Lillesand (International Journal of Remote Sensing, 2007)

Himalayan glacier retreat using IRS 1C PAN stereo data - I. M. Bahuguna; A. V. Kulkarni; Shailesh Nayak; B. P. Rathore; H. S. Negi; P. Mathur (International Journal of Remote Sensing, 2007)

Genotyping of urinary and fecal Proteus mirabilis isolates from individuals with long-term urinary catheters - S. Mathur; N. A. Sabbuba; M. T. E. Suller; D. J. Stickler; R. C. L. Feneley (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Late Archean Cu-Au-Mo mineralization at Gameleira and Serra Verde, Carajs Mineral Province, Brazil: constraints from Re-Os molybdenite ages - Robert Marschik; Ryan Mathur; Joaquin Ruiz; Richard A. Leveille; Antonio-Jos de Almeida (Mineralium Deposita, 2005)

Genetic transformation technology: Status and problems - Kiran K. Sharma; Pooja Bhatnagar-Mathur; Trevor A. Thorpe (In Vitro Cellular & Developmental Biology - Plant, 2005)

Differential morphogenetic responses, ginsenoside metabolism and RAPD patterns of three Panax species - A. Mathur; A.K. Mathur; R.S. Sangwan; A. Gangwar; G.C. Uniyal (Genetic Resources and Crop Evolution, 2003)

Carbon and oxygen isotope profiles from the terminal precambrian Marwar Supergroup, Rajasthan, India - Anil Maheshwari; A. N. Sial; S. C. Mathur (Carbonates and Evaporites, 2003)

Intercomparison of IRS-P4-MSMR derived geophysical products with DMSP-SSM/I and TRMM-TMI finished products - A. K. Varma; R. M. Gairola; A. K. Mathur; B. S. Gohil; Vijay K. Agarwal (Journal of Earth System Science, 2002)

Rain rate measurements over global oceans from IRS-P4 MSMR - A. K. Varma; R. M. Gairola; Samir Pokhrel; B. S. Gohil; A. K. Mathur; Vijay K. Agarwal (Journal of Earth System Science, 2002)

Field based spectral reflectance studies to develop NDSI method for snow cover monitoring - A V Kulkarni; J Srinivasulu; S S Manjul; Mathur P (Journal of the Indian Society of Remote Sensing, 2002)

Carbon isotope fluctuations through the neoproterozoic-lower Cambrian Birmania basin, Rajasthan, India - Anil Maheshwari; A. N. Sial; S. C. Mathur (Carbonates and Evaporites, 2002)

Development of the Regional Policy Process for Air Pollution in South Asia, Southern Africa and Latin America - W. Kevin Hicks; Johan C.I. Kuylenstierna; Vikrom Mathur; Sergio Mazzucchelli; Viviana Burijson; Surendra Shrestha; Mylvakanam Iyngararasan; Stephen Simukanga; A. Mieke Van Tienhoven (Water, Air, & Soil Pollution, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Biochemical and morphological changes in some organs of rats in nickel intoxication - A. K. Mathur; Satya V. Chandra; Jairaj Behari; S. K. Tandon (Archives of Toxicology, 1977)